Whole-body MR imaging in the German National Cohort: rationale, design, and technical background - Bamberg, Fabian; Kauczor, Hans-Ulrich; Weckbach, Sabine; Schlett, Christopher L.; Weber, Marc-André; Kaaks, Rudolf (Radiology, 2015)
PurposeTo detail the rationale, design, and future perspective of implementing whole-body magnetic resonance (MR) imaging in the German National Cohort, a large multicentric population-based study.Materials and MethodsAll institutional review boards approved the study, and informed consent is obtained before study enrollment. Participants are enrolled from a random sample of the general population at five dedicated imaging sites among 18 recruitment centers. MR imaging facilities are equipped with identical 3.0-T imager technology and use uniform MR protocols. Imager-specific hardware and software settings remained constant over the study period. On-site and centralized measures of image quality enable monitoring of completeness of the acquisitions and quality of each of the MR sequences. Certified radiologists read all MR imaging studies for presence of incidental findings according to predefined algorithms. ResultsOver a 4-year period, six participants per day are examined at each center, totaling a final imaging cohort of approximately 30 000 participants. The MR imaging protocol is identical for each site and comprises a set of 12 native series to cover neurologic, cardiovascular,thoracoabdominal, and musculoskeletal imaging phenotypes totaling approximately 1 hour of imaging time. A dedicated analysis platform as part of a central imaging core incorporates a thin client-based integrative and modular data handling platform to enable multicentric off-site image reading for incidental findings. Scientific analysis will be pursued on a per-project hypothesis-driven basis.ConclusionPopulation-based whole-body MR imaging as part of the German National Cohort will serve to compile a comprehensive image repository, will provide insight into physiologic variants and subclinical disease burden, and has the potential to enable identification of novel imaging biomarkers of risk.© RSNA, 2015Online supplemental material is available for this article.
Gesehen am 30.07.2020